Study of Government Regulation Number 23 of 2018 In Order to Minimize Tax Avoidance GAPS - Suparna Wijaya; Ferry Irawan; Andri Marfiana; Suripto Suripto; Tomi Hadi Lestiyono (Budapest International Research and Critics University, 2022)
Tax avoidance is assumed to be one of the causes why the government could not achieve the tax revenues. On the other hand, it also lowers the tax ratio. The purpose of this study is to examine Government Regulation Number 23 of 2018 in order to minimize tax avoidance loopholes. The research method used is qualitative with a thematic approach. The results of the study indicate that tax avoidance is an instrument to minimize tax payments by taking advantage of loopholes in the legislation. Government Regulation Number 23 of 2018 is a provision issued by the government in order to provide convenience for taxpayers to be able to fulfill their tax obligations. In addition, the provision of a lower tariff of 0.5% is expected to increase disposable income. Furthermore, this disposable income can gradually increase gross domestic income, and further increase the taxation base in general. However, the application of Government Regulation Number 23 of 2018 can be utilized by taxpayers to minimize the tax burden that must be paid. This study provides two important recommendations they are: further regulation regarding commercial operations, and provisions regarding freelance work.